Millennial cold–dry events during marine isotope stage 11a based on sedimentary records from the Heqing Basin and their global climatic dynamical responses - Guohui Liu; Xinwen Xu; Shenghui Wang; Lirong Hou; Yuqing Zhang; Liu Yang; Jingfang Zhang; Yuzhu Zhang; Hui Zhao; Chaofeng Fu; Xiaoke Qiang; Wen Liu; et al. (Global and Planetary Change, 2026)

In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

Liraglutide affects mitochondrial function and histone acetylation through the NQO1/SIRT3 pathway in diabetic kidney disease - Jie Gao; Xiaoyu Lv; Pingping Zhao; Bingjing Pan; Jingfang Liu (Molecular and Cellular Biochemistry, 2026)

An adaptive hybrid modeling approach integrating elastic net and Kriging for activated sludge treatment - Yaohui Li; Zebin Zhang; Zhifeng Yin; Jingfang Shen; Wenwei Liu (Environmental Research, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

MnSO₄-synergized oyster shell powder outperforms rice straw in mediating dual abiotic and microbial pathways for paddy cd remediation - Guofei Liu; Jingfang Li; Weixiong Jiao; Ye Li; Xiaoyuan Yin; Dasong Lin (Chemical Engineering Journal, 2026)

Pupil dynamic adaptation in response to environmental luminance: A controlled laboratory study - Qing Pan; Shoujie Zhang; Jingfang Bian; Tao Luo; Minchen Wei; Peng Xue; Jingchao Xie; Jiaping Liu (Building and Environment, 2026)

Cross-scale long-term spatiotemporal dynamics and influencing indicators of summer urban heat risk in mega-urban agglomeration - Jiachen Liu; Xiaofang Wang; Jingfang Yan; Xinfei Zhao; Wenke Chen; Le Yin; Baolei Zhang (Journal of Cleaner Production, 2025)

Advancing carbon neutrality through innovative soil remediation strategies: Co-application of materials and MnSO4 for cadmium-contaminated paddy soils - Guofei Liu; Yanru Zhang; Zhehan Li; Weixiong Jiao; Jingfang Li; Xiaoyuan Yin; Dasong Lin (Journal of Environmental Chemical Engineering, 2025)

An integrated mechanistic modeling and machine learning for radio frequency heating uniformity optimization of canola seeds - Jilong Gao; Yu Liu; Jingfang Ao; Shaojin Wang; Jiajia Chen; Long Chen (Innovative Food Science & Emerging Technologies, 2025)

Dendritic-honeycomb porous polyoxometalate/MXene films for supercapacitor applications - Xinzheng Li; Yingyi Ma; Xinran Li; Yu Si; Kexin Liu; Shiyun Wang; Zhihao Zhu; Jingfang Li (Chemical Engineering Journal, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

In situ construction "Metabolism-Immunity" crosstalk rewiring bioreactor with single-dose mitochondria energizing hydrogel for amplifying T cell fitness and anti-tumor immunity - Hongting Liu; Xinping Luo; Honghao Sun; Jingfang Pan; Siqian Ding; Zhanwei Zhou; Minjie Sun (Chemical Engineering Journal, 2025)

The roles of flaxseed gum and its oligosaccharides as stabilizers in zein nanoparticles for apigenin delivery: Stability, antioxidant activity, bioavailability, molecular simulations - Yufei Liu; Ziliang Li; Shuaijun Lu; Shang Gao; Mengting Xu; Ze Yuan; Yue Li; Yiqiao Gao; Jingfang Shangguan; Xia Xiang (Food Chemistry, 2025)

Mitofusin 2 Mediates the Protective Effect of NR6A1 Silencing Against Neuronal Injury in Experimental Stroke Models - Bingtian Xu; Zhuhe Liu; Kechun Chen; Qian Zhao; Haixia Wen; Jingfang Lin; Jiangping Xu; Haitao Wang; Honghao Wang; Yuanyuan Wang (Molecular Neurobiology, 2025)

Protective effect of astragaloside IV against zinc oxide nanoparticles induced human neuroblastoma SH-SY5Y cell death: a focus on mitochondrial quality control - Liwei Wang; Lu Zhang; Yang Yun; Tingting Liang; Chaoqun Yan; Zhuoya Mao; Jingfang Zhang; Baoshe Liu; Jian Zhang; Taigang Liang (Molecular and Cellular Biochemistry, 2025)

Comprehensive study of heavy precipitation events over land using climate network analysis - Kaiwen Li; Ming Wang; Kai Liu; Jingfang Fan (Journal of Hydrology, 2025)

Synchronization patterns of extreme rainfall events in Southwest China - Panjie Qiao; Xiaojuan Wang; Wenqi Liu; Shuai Li; Yongwen Zhang; Guolin Feng; Jingfang Fan (Climatic Change, 2025)

Oxymatrine reduces hepatic lipid synthesis in rat model of nonalcoholic steatohepatitis by regulating Sirt1/AMPK and LXR/Plin2/SREBP-1c pathways - Jingfang Xiong; Gaofeng Chen; Ying He; Changqing Zhao; Dongya Chen; Yihui Liu; Zhaolin Zhang; Yijun Wu; Hong Xu (Chemico-Biological Interactions, 2025)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Rock-mass heterogeneous rheological properties caused the formation of deep tension fractures - Guoqing Chen; Xiang Sun; Qiang Xu; Sihong Zeng; Jingfang Xing; Xuemin Feng; Fangzhou Liu (Geomechanics for Energy and the Environment, 2024)

SIRT3: A Potential Target of Different Types of Osteoporosis - Binjing Pan; Chongyang Chen; Yangting Zhao; Jing Cai; Songbo Fu; Jingfang Liu (Cell Biochemistry and Biophysics, 2024)

A two-photon fluorescent probe for highly selective detection of Cys over GSH and Hcy based on the Michael addition and transcyclization mechanism and its application in bioimaging and protein straining in SDS-PAGE - Qi Sun; Ting Zhang; Yuchen Ren; Yuan Qiu; Xiaogang Luo; Jingfang Yang; Genyan Liu (Analytica Chimica Acta, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Substrate specificity of polyphenol oxidase and its selectivity towards polyphenols: Unlocking the browning mechanism of fresh lotus root (Nelumbo nucifera Gaertn.) - Jingfang Li; Ze-yuan Deng; Huanhuan Dong; Rong Tsao; Xiaoru Liu (Food Chemistry, 2023)

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

Vegetation restoration enhances soil erosion resistance through decreasing the net repulsive force between soil particles - Rentian Ma; Feinan Hu; Chenyang Xu; Jingfang Liu; Zhenghong Yu; Gang Liu; Shiwei Zhao; Fenli Zheng (CATENA, 2023)

Effects of nitrogen and phosphorus supply levels and ratios on soil microbial diversity-ecosystem multifunctionality relationships in a coastal nontidal wetland - Kai Sun; Jingfang Cai; Xiaoling Liu; Lijuan Yang; Hongli Li; Guangmei Wang; Xingliang Xu; Feihai Yu (Science of The Total Environment, 2023)

Evaluation of novel isolates of Lacticaseibacillus rhamnosus Probio-M9 derived through space mutagenesis - Jingfang Yang; Yue Sun; Xueyan Lei; Lixia Zhao; Rui Luo; Wenjun Liu (Food Bioscience, 2023)

The inhibitory mechanism of pentacyclic triterpenoid acids on pancreatic lipase and cholesterol esterase - Heyu Shen; Jun Wang; Jingfang Ao; Lixia Ye; Yubing Shi; Yujie Liu; Mengyang Li; Anwei Luo (Food Bioscience, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

Evaluating the effect of soil internal forces on the stability of natural soil aggregates during vegetation restoration - Rentian Ma; Feinan Hu; Jingfang Liu; Shiwei Zhao (Journal of Soils and Sediments, 2021)

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice - Tingting Hu; Yunlu Tian; Jianping Zhu; Yunlong Wang; Ruonan Jing; Jie Lei; Yinglun Sun; Yanfang Yu; Jingfang Li; Xiaoli Chen; Xiaopin Zhu; Yuanyuan Hao; et al. (Plant Cell Reports, 2018)

NAC transcription factor ONAC066 positively regulates disease resistance by suppressing the ABA signaling pathway in rice - Qing Liu; Shijuan Yan; Wenjie Huang; Jianyuan Yang; Jingfang Dong; Shaohong Zhang; Junliang Zhao; Tifeng Yang; Xingxue Mao; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2018)

Characterization and genomic analyses of Aeromonas hydrophila phages AhSzq-1 and AhSzw-1, isolates representing new species within the T5virus genus - Shengjian Yuan; Ling Chen; Quan Liu; Yan Zhou; Jingfang Yang; Deng Deng; Hongping Li; Yingfei Ma (Archives of Virology, 2018)

Complete genome sequence of a novel lytic bacteriophage isolated from Ralstonia solanacearum - Jingfang Su; Hongwei Sun; Junjie Liu; Zhaokui Guo; Guoquan Fan; Gang Gu; Guanghua Wang (Archives of Virology, 2017)

The germin-like protein OsGLP2-1 enhances resistance to fungal blast and bacterial blight in rice - Qing Liu; Jianyuan Yang; Shijuan Yan; Shaohong Zhang; Junliang Zhao; Wenjuan Wang; Tifeng Yang; Xiaofei Wang; Xingxue Mao; Jingfang Dong; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2016)

Functional evaluation of four putative DNA-binding regions in Thermoanaerobacter tengcongensis reverse gyrase - Jie Li; Jingfang Liu; Jian Zhou; Hua Xiang (Extremophiles, 2011)

Complete sequence and molecular characterization of pNB101, a rolling-circle replicating plasmid from the haloalkaliphilic archaeon Natronobacterium sp. strain AS7091 - Meixian Zhou; Hua Xiang; Chaomin Sun; Yun Li; Jingfang Liu; Huarong Tan (Extremophiles, 2004)

Thermostable esterase from Thermoanaerobacter tengcongensis: high-level expression, purification and characterization - Jian Zhang; Jingfang Liu; Jian Zhou; Yuanyuan Ren; Xiuyu Dai; Hua Xiang (Biotechnology Letters, 2003)